Mesenchymal Stem Cell-Specific and Preosteoblast-Specific Ablation of TSC1 in Mice Lead to Severe and Slight Spinal Dysplasia, Respectively. (27th March 2020) - Yang, Cheng; Liao, Jianwen; Lai, Pinglin; Huang, Hai; Fan, Shicai; Chen, Yuhui; Bai, Xiaochun
Abstract : Background . TSC1-related signaling plays a pivotal role in intramembranous and endochondral ossification processes during skeletogenesis. This study was aimed at determining the significance of the TSC1 gene at different stages of spinal development. Materials and Methods . TSC1-floxed mice (TSC1 flox/flox ) were crossed with Prrx1-Cre or BGLAP-Cre transgenic mice or mesenchymal stem cell- and osteoblast-specific TSC1-deficient mice, respectively. Somatic and vertebral differences between WT and Prrx1-TSC1 null mice were examined at 4 weeks after birth. Results . No apparent body size abnormalities were apparent in newborn and 4-week- to 2-month-old mice with BGLAP-Cre driver-depleted TSC1. Vertebral and intervertebral discs displayed strong dysplasia in Prrx1-TSC1 null mice. In contrast, vertebrae were only slightly affected, and intervertebral discs from skeletal preparations displayed no apparent changes in BGLAP-TSC1 null mice. Conclusion . Our data suggest that the TSC1 gene is crucial for endochondral ossification during postnatal spine development but plays discriminative roles at different stages. Mesenchymal stem cell-specific ablation of TSC1 led to severe spinal dysplasia at early stages of endochondral ossification while osteoblast-specific deletion of TSC1 affected vertebrae slightly and had no detectable effects on intervertebral discs.